ANTIPROLIFERATIVE PROPERTIES OF AQUEOUS Labisia pumila EXTRACT ON PROSTATE CANCER CELL LINES (Jurnal Teknologi (Sciences & Engineering), 2015)
Labisia pumila or locally known as Kacip Fatimah has been widely used by women in Malaysia to treat post-partum illnesses. This herbaceous undershrub of the Myrsinaceae family has been exploited aggressively as beverages, cosmetics as well as health supplement to promote wellness in the past. This present study was to determine the anti-proliferative properties of L. pumila aqueous extract against prostate cancer cell lines and to identify the active compound which may contribute to the anti-proliferative activity of L. pumila. In this study, the aqueous extract was prepared by using ultrasound assisted extraction method. The preliminary result revealed that L. pumila aqueous extract inhibited the proliferation of the prostate cancer cell lines. The aqueous extract was further fractionated using column chromatography. The result from the scavenging activity test confirmed that L. pumila crude extract and its fraction (F2) displayed a strong activity with 70% inhibition. Total phenolic contents assay was carried out to determine the phenolic compound of the extract and its fractions and the results showed the total phenolic content was higher in the F2 (96.82±0.3 GAE mg/g) compared to crude (63.75±0.1 GAE mg/g) and F1 (73.75±0.1 GAE mg/g). In conclusion, these findings suggested that the crude and fraction (F2) of L. pumila contain phenolic compounds that act as anti-proliferative agent against proliferation of prostate cancer cell lines in vitro.